Leisure time behaviors: Prevalence, correlates and associations with overweight in Brazilian adults. A cross-sectional analysis - Fernandes, Romulo A. [UNESP] (2010)
Background: Television viewing (TV viewing) is an important indicator of physical inactivity. Aim: To analyze the prevalence of different leisure time behaviors and TV viewing among healthy adults and their association with overweight. Material and Methods: Cross sectional survey in which 1061 females and 925 males aged 30 years old or more, answered a self administered questionnarie about physical activity. Respondents were classified according to frequency participation in sports, walking, cycling and TV viewing. Body mass index (BMI) was derived from self reported weight and height. Results: Less than 30% of individuals participated regularly in sports and less than 15 and 5% reported a high frequency of walking and cycling, respectively. Subjects regularly engaged in sports had a lower BMI. After adjustments, low cycling frequency and high TV viewing were associated with overweight in men and women, respectively. Conclusions: The prevalence of physical inactivity during leisure time is high among Brazilian adults and associated to obesity. (Rev Med Chile 2010; 138: 29-35).